2021
DOI: 10.1126/sciadv.abh2169
|View full text |Cite
|
Sign up to set email alerts
|

A single–cell type transcriptomics map of human tissues

Abstract: Advances in molecular profiling have opened up the possibility to map the expression of genes in cells, tissues, and organs in the human body. Here, we combined single-cell transcriptomics analysis with spatial antibody-based protein profiling to create a high-resolution single–cell type map of human tissues. An open access atlas has been launched to allow researchers to explore the expression of human protein-coding genes in 192 individual cell type clusters. An expression specificity classification was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
729
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 902 publications
(912 citation statements)
references
References 34 publications
30
729
0
Order By: Relevance
“…Transcripts in blood could indicate expression by blood cells or could reflect the presence of circulating EC. In 2 body-wide human single-cell atlases 48 , 49 and 1 single-cell database (of both mouse and human studies), 50 the majority of the 38 candidates were enriched in EC; 20/38 (53%) in 2 or all, with 25/38 (66%) in at least 1 (Table I, Tab_5, Table A, column O, P, Q in the Data Supplement ). Transcripts encoding for 13/38 candidates (34%) were enriched in immortalized EC, versus other cell lines (Table I, Tab_5, Table A, column S in the Data Supplement ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcripts in blood could indicate expression by blood cells or could reflect the presence of circulating EC. In 2 body-wide human single-cell atlases 48 , 49 and 1 single-cell database (of both mouse and human studies), 50 the majority of the 38 candidates were enriched in EC; 20/38 (53%) in 2 or all, with 25/38 (66%) in at least 1 (Table I, Tab_5, Table A, column O, P, Q in the Data Supplement ). Transcripts encoding for 13/38 candidates (34%) were enriched in immortalized EC, versus other cell lines (Table I, Tab_5, Table A, column S in the Data Supplement ).…”
Section: Resultsmentioning
confidence: 99%
“…Data from human single-cell atlases 48 , 49 and the Panglao database ( https://panglaodb.se ) 50 were used to provide EC protein expression information in Table I, Tab 5 in the Data Supplement .…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the cardiovascular system, cardiomyocytes, endothelial cells, fibroblasts, smooth muscle cells and immune cells are relevant. Several enzymes are expressed in these cells, for detailed information see Supplement Table healthy human tissues (Supplement Table 1) according to transcriptomics datasets of www.proteinatlas.org (28). The ratelimiting IDO expression is not detected in cardiomyocytes, fibroblasts and dendritic cells, and expression is low in endothelial, smooth muscle and T cells, and high in macrophages and monocytes (Supplement Table 1) in healthy persons.…”
Section: The Kynurenine Pathwaymentioning
confidence: 99%
“…In this study, we found that knocking out the PIGS and HRD1 genes caused the accumulation of CD55 precursor proteins, which enabled us to reveal the speci c role of the GPI attachment signal peptide of CD55 in GPI biosynthesis. It is reasonable to postulate that CD55 acts as a regulator because it is widely expressed in diverse organs and cells 52 . Moreover, we found that the GPI attachment signal peptide of CD48 functioned similarly to that of CD55.…”
Section: Discussionmentioning
confidence: 99%